Handbook of nuclear chemistry - Vertes, Attila; Nagy, Sandor; Klencsar, Zoltan; Lovas, Rezso G.; Rosch, Frank; SpringerLink (Online service). (Dordrecht Heidelberg Springer, 2011)
This revised and extended 6 volume handbook set is the most comprehensive and voluminous reference work of its kind in the field of nuclear chemistry. The Handbook set covers all of the chemical aspects of nuclear science starting from the physical basics and including such diverse areas as the chemistry of transactinides and exotic atoms as well as radioactive waste management and radiopharmaceutical chemistry relevant to nuclear medicine. The nuclear methods of the investigation of chemical structure also receive ample space and attention. The international team of authors consists of scores of world-renowned experts - nuclear chemists, radiopharmaceutical chemists and physicists - from Europe, USA, and Asia. The Handbook set is an invaluable reference for nuclear scientists, biologists, chemists, physicists, physicians practicing nuclear medicine, graduate students and teachers - virtually all who are involved in the chemical and radiopharmaceutical aspects of nuclear science. The Handbook set also provides further reading via the rich selection of references.
v. 1. Basics of nuclear science -- v. 2. Elements and isotopes : formation, transformation, distribution -- v. 3. Chemical applications of nuclear reactions and radiations -- v. 4. Radiochemistry and radiopharmaceutical chemistry in life sciences -- v. 5. Instrumentation, separation techniques, environmental issues -- v. 6. Nuclear energy production and safety issues.
Electronic reproduction.
Keywords: Nuclear chemistry; Electronic books